PELAKSANAAN KEWENANGAN PEMERINTAH KOTA PEKENBARU TERHADAP PENYALAHGUNAAN IZIN MOVIE BOX DI KOTA PEKANBARU BERDASARKAN PERDA NOMOR 3 TAHUN 2002 TENTANG HIBURAN UMUM - Afandi, Irfan; Firdaus, Emilda; Artina, Dessy (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
With the enactment of Law Number 3 of 2002 concerning RegionalGovernments, regions are required to organize their own government and managetheir regions in the hope of accelerating the creation of public welfare. The birthof a general policy is a step taken by the government to resolve public issues. insociety. Policy is a patterned action intended to achieve certain goals. In an effortto maintain security, order and stability in development and pay attention to theevolving aspirations in the religious and cultured society of Pekanbaru City.The problem that the author makes the basis of this research is how theimplementation of the authority of the Pekanbaru City government against themisuse of the Movie Box permit in Pekabaru City, are the inhibiting factors facedby the Pekanbaru City government in exercising authority over the Movie Box inPekanbaru City and how the Government has made efforts City of Pekanbaruagainst abuse of Movie BoX permits in Pekanbaru CityThis research was conducted at the Pekanbaru City Satpol and the IntegratedOne Door Investment Service, the data sources used were: primary data andsecondary data, data collection techniques in this study by observation, interviewsand literature review.The results of this study are first. The implementation of the authority of thePekanbaru city government against the abuse of movie box permits in the city ofPekanbaru is not yet in accordance with what should be done by the Pekanbarucity government or not yet optimal, there are still many violations related tooperational hours and as a place of prostitution by some people, proving thatcitizenship Pekanbaru city government is not yet in line with what is expected ornot optimal. The two factors inhibiting the implementation of the policy ofPekanbaru City government are as follows: communication and resources, thethree efforts made by Pekanbaru City Government in overcoming the abuse ofMovie Box permits in Pekanbaru City by first conducting surveillance towards theMovie Box, the second performs a inspection of the Movie Box, the third writesthe Movie Box that violates permissions and finally takes actions such as closingtemporarily the Movie Box that violates permissions or closes forever Lahipermission.Keywords: permission, supervision, policy, Movie Box